PENERAPAN METODE FOLKTALE BASED STORYTELLING DALAM MENGAJARKAN KETERAMPILAN BERBICARA MAHASISWA DI INSTITUT PENDIDIKAN TAPANULI SELATAN - Gabby Maureen Pricilia; Habib Rahmansyah (Institut Pendidikan Tapanuli Selatan, 2020)
The purposes of this research are to find out: 1) the extent of students’ speaking ability, and 2) the significant effect of using folktale based stotytelling on students’ speaking ability at the second semester students of english department in Institut Pendidikan Tapanuli Selatan. The research methodology is quantitative method. The researcher collected the data by using oral test. The sample was taken by using total sampling technique, it was 24 students. The data were then analyzed by using descriptive and inferential analysis, it was t-test formula by Arikunto. The results of the research are the mean score of students’ speaking ability before using using folktale based stotytelling was 51.5 which categorized “less”, then after using using folktale based stotytelling was 72.37 which categorized “good”. The hypothesis testing showed that t-test was higher than t-table (17 > 2.04), it means that the hypothesis is accepted. The finding of research reveals that there is a significant effect of using folktale based stotytelling on students’ speaking ability at the second semester students of english department in Institut Pendidikan Tapanuli Selatan.